2014
DOI: 10.7314/apjcp.2014.15.2.713
|View full text |Cite
|
Sign up to set email alerts
|

Does HBV Infection Increase Risk of Endometrial Carcinoma?

Abstract: Objective: Connections between chronic inflammation and tumor development and progression are now generally accepted. Recent evidence indicates that hepatitis B is associated with several types of cancer, but whether endometrial carcinoma (EC) is included has not been reported. Methods: We analyzed HBV serum marker status in 398 patients with endometrial cancer, comparing them to 788 control women undergoing health examination. Results: The total prevalence of HBsAg tested positive in cancer group was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…As uterine causes in our database were inclusive of many different conditions from congenital anomalies such as uterine septum to other conditions like uterine fibroids, adenomyosis, polyps, and adhesions, the small numbers of all these conditions individually did not allow us to distinguish whether the association was with one or more specific conditions, and a study of much larger sample size with focus on uterine factors would be necessary to clarify the association. Nevertheless, this association deserves further investigation as a correlation between HBV infection with endometrial carcinoma was recently reported . More unexpectedly was the failure to demonstrate an association between HBV infections in the male partners with male infertility.…”
Section: Discussionmentioning
confidence: 92%
“…As uterine causes in our database were inclusive of many different conditions from congenital anomalies such as uterine septum to other conditions like uterine fibroids, adenomyosis, polyps, and adhesions, the small numbers of all these conditions individually did not allow us to distinguish whether the association was with one or more specific conditions, and a study of much larger sample size with focus on uterine factors would be necessary to clarify the association. Nevertheless, this association deserves further investigation as a correlation between HBV infection with endometrial carcinoma was recently reported . More unexpectedly was the failure to demonstrate an association between HBV infections in the male partners with male infertility.…”
Section: Discussionmentioning
confidence: 92%
“…[5][6][7]19,20 We also reported that HBV infection increased synchronous liver metastasis rate and was an independent prognostic factor in pancreatic cancer patients. 21 Moreover, there were some sporadic studies showing that HBV infection might be associated with gastric cancer, 12 nasopharyngeal carcinoma, 14 endometrial carcinoma 22 and distal colon adenoma. 23 Our study verified the modest but significant association with non-hepatocellular cancers, including NHL, pancreatic cancer, cholangiocarcinoma, gastric cancer and nasopharyngeal carcinoma, in a large cohort of Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that HBV was detected in diverse cell types, including endothelial cells, mucosal epithelial cells, macrophages/ monocytes and hematopoietic precursors, implying that HBV was likely to exist in the lung (Mason et al, 1993). Chronic exposure to HBV was probable to give rise to alteration in cellular immunity, leading to tumorigenesis and promoting cancer aggressiveness (De et al, 2010;Engels et al, 2010;Srivatanakul et al, 2010;Li et al, Zhu et al, 2011;Jiang et al, 2014). It is inferred that alteration in cellular immunity due to chronic HBV stimulation may be involved in influencing biological behavior of cancer cells.…”
Section: )mentioning
confidence: 99%